Karakteristik hidrolisat kolagen kulit ikan tenggiri kering dengan enzim papain: The characteristics of spanish mackerel dry skin collagen hydrolisate with papain enzyme - Rahmawati, Hafni; Agustini, Tri Winarni; Dewi, Eko Nurcahya; Trianto, Agus (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Spanish mackerel dried skin is commonly used in chips, crackers, and empek-empek products. However, its potential for transformation into value-added products such as collagen hydrolysate still needs to be explored. Processing this material using papain enzyme offers an efficient method to enhance its economic value, owing to its high yield and effectiveness. The aim of this study was to determine the optimum concentration of papain enzyme and soaking time for the hydrolysis of dried mackerel skin collagen based on the characteristics of dried mackerel skin collagen. This study applied a completely randomized design (CRD) with two factors: papain enzyme concentration (1% and 2%) and soaking time (12 and 24 h). The results indicated that the interaction between enzyme concentration and soaking time significantly affected key parameters, including hydrolysis degree, whiteness, protein content, viscosity, gel strength, melting point, solubility, and foaming ability, whereas yield, moisture, ash, fat, pH, and zeta potential were unaffected. Optimal conditions were achieved with 2% papain enzyme and 24-hour soaking time, resulting in a 2.30% yield, 35.62% hydrolysis degree, 77.73% white degree, 6.94% moisture, 1.44% ash, 95.35% protein, 2.33% lipid, 6,13cp viscosity, 46.64 gBloom gel strength, 14.67OC melting point, 5.83 pH, 2.47mV zeta potential, 82.00% solubility, and 31.67% foaming ability. These results highlight the significant potential of Spanish mackerel dried skin as a raw material for collagen hydrolysate production, supporting its application in developing high-value fishery by-products and promoting sustainable economic development.